Makna Patriarki Dalam Konsep Fiqh Mawaris - Hartinah Aprilia; Ria Astina (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Islam itself came to earth with a mission to glorify humans by including the positions of both," he explained. An attitude of fairness, equality and mutual respect for fellow human beings without being based on differences is one of the teachings of Islam. Thus, patriarchal culture is not in accordance with Islam: the meaning of justice in Islamic inheritance law is not measured by the equality of levels between heirs, but is determined based on the size of the burden or responsibility assigned to them, in terms of the generality of human conditions/life. In Muslim society, men are responsible for providing for their families, different from women. If the woman is a girl or is still unmarried, then she is the responsibility of her parents or guardian or her brother. Meanwhile, after a woman marries, her moving will be the responsibility of her husband (man). The type of research in this research is the approach used in this research is the normative juridical method, namely legal research carried out by prioritizing examining library materials or documents called secondary data, in the form of primary, secondary and tertiary legal materials. Many people claim that Islamic inheritance law discriminates against women, this is due to differences in distribution ratios in inherited assets. As is known, the ratio between men and women in Islamic inheritance law is 2:1, which means that the share of property received by men is greater than that of women, so many people say that Islamic inheritance law is unfair and gender unequal. . In fact, it is necessary to review the meaning of what is fair and gender equal, as explained in this research, that fairness is putting things in their proper place, this does not mean that fairness is equal, while gender equality means having the same conditions for men and women to obtain the same opportunities and rights as humans.